1980
DOI: 10.1128/iai.27.3.928-937.1980
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics and pathogenesis of experimental Pneumocystis carinii pneumonia

Abstract: Pneumocystis carinii pneumonia was produced in two groups of rats by the administration of corticosteroids, a low-protein (8%) diet, and tetracycline in the drinking water. A third group not on corticosteroids or a low-protein diet served as controls. Members of the first group were sacrificed weekly for 8 weeks, and lungs were examined. A highly significant correlation was found between the histopathological assessment of the intensity of P. carinii infection and the number of cysts counted in enzyme-digested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
1

Year Published

1980
1980
1997
1997

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(25 citation statements)
references
References 32 publications
3
21
0
1
Order By: Relevance
“…On histopathologic examination, the alveoli showed the typical foamy eosinophilic material, but the host inflammatory response was mild and nonspecific. These features are similar to those found in previous studies of P. carinii pneumonia in nude mice and in corticosteroid-treated normal mice and rats (37,38,43).…”
Section: Discussionsupporting
confidence: 89%
“…On histopathologic examination, the alveoli showed the typical foamy eosinophilic material, but the host inflammatory response was mild and nonspecific. These features are similar to those found in previous studies of P. carinii pneumonia in nude mice and in corticosteroid-treated normal mice and rats (37,38,43).…”
Section: Discussionsupporting
confidence: 89%
“…There are fundamental problems with the animal model in separating the cellular and biochemical observations associated with the immunosuppression from those associated with PCP (because all of the immunosuppressed animals developed PCP) and in identifying the activities associated with P. carinii from those associated with the lung parenchyma and the cells of the immune system. In spite of these limitations, it was found that the experimental PCP described here was histopathologically similar to the classical textbook description; namely, it was characterized by an increased width of alveolar septa, the existence of perialveolar and diffuse fibroses, and the presence of intra-alveolar eosinophilic material and an exudate containing macrophages and interstitial mononuclear cell infiltrates (8,41). Ultrastructurally, type I epithelial cells showed signs of degeneration and the formation of subepithelial blebs between the type I cells and the basal lamina.…”
Section: Discussionsupporting
confidence: 53%
“…It is characterized clinically by dyspnea, tachypnea, and hypoxemia (5,11,12). The lung tissue is usually diffusely involved, with the alveoli becoming filled with a foamy, proteinaceous material (41). This foamy debris effectively diminishes the alveolar surface area available for gas exchange and therefore causes shunting of unoxygenized blood with a resultant disturbed ventilation-perfusion ratio and hypoxemia (21).…”
mentioning
confidence: 99%
“…On the other hand, Giemsa stains a variety of host cells, sometimes making it difficult to distinguish P. carinii; the small size of trophozoites and their tendency to clump have precluded accurate quantitation of this form of the organism. We and others have found that counting the number of cysts by the use of cell wall stains provides the most reliable marker of the number of Pneumocystis organisms (28,39,40).…”
Section: Discussionmentioning
confidence: 94%